Pre-operative habitual dietary fibre stratifies 12-week immune–inflammatory recovery after oesophagectomy: a multicentre prospective cohort study - Li, Yang; Chen, Yuan; Guo, You; Wu, Ling; Sun, Hu; Wang, Danqiong; Li, Tao; An, Na; Yan, Jingfang (Frontiers in Nutrition, 2025)
ObjectivesTo test whether habitual pre-operative dietary fibre predicts 12-week immune–inflammatory recovery after oesophagectomy.MethodsWe conducted a multicentre prospective cohort across three tertiary hospitals. Adults with resectable oesophageal cancer completed a validated FFQ; total fibre (energy-adjusted) was grouped into sex-specific quartiles. Prespecified week-12 endpoints were: (i) a favourable inflammatory profile (CRP within reference or ≥50% fall plus NLR ≤ 3.0) and (ii) lymphocyte recovery (≥30% rise or ≥1.5 × 10^9·L−1). Robust Poisson models (clustered by site) estimated adjusted relative risks; dose–response was expressed per 10 g·day−1. Longitudinal biomarker trajectories (baseline→post-operative day 7 → week 12) used mixed-effects models.ResultsAmong 312 participants, event rates increased monotonically with higher fibre. Versus Q1, adjusted RRs for the favourable inflammatory profile were 2.36 (1.85–3.01) in Q3 and 2.62 (2.20–3.12) in Q4; for lymphocyte recovery, 1.63 (1.39–1.92) and 1.79 (1.65–1.95), respectively. Each +10 g·day−1 of fibre associated with RR 1.56 (1.34–1.82) for the favourable profile and 1.30 (1.17–1.45) for lymphocyte recovery. CRP and NLR declined more steeply and lymphocyte counts rose more in higher-fibre groups (time×quartile p = 1.68 × 10−4; 1.21 × 10−4; 2.26 × 10−10). Early infections and 30-day mortality did not differ convincingly (per-10 g RR 0.84, p = 0.333; overall 1.0%). FFQ–record ICC for fibre was 0.87.ConclusionHigher habitual fibre before surgery was associated with materially better week-12 immune–inflammatory recovery after oesophagectomy, with consistent dose–response and longitudinal signals across centres. Routine pre-operative fibre appraisal offers a low-cost, clinic-ready stratifier for counselling and prehabilitation; interventional studies should test whether augmenting habitual fibre improves recovery trajectories.